I'm trying to do the following exercise:

Prove that $\forall n \in \Bbb{N}, 1 <n, \biggl( 1 + \frac{1}{n}$ $\biggr)^n < \sum_{i=0}^n \frac{1}{i!}$

(I can't use limits, e, or any other tool from calculus)

The textbook where I found this suggests using the binomial theorem.

This is what I've got so far:

$\biggl( 1 + \frac{1}{n} \biggr)^n = \sum_{i=0}^n \binom{n}{i} (\frac{1}{n})^i$

Therefore $ \biggl( 1 + \frac{1}{n} \biggr)^n < \sum_{i=0}^n \frac{1}{i!} \iff \sum_{i=0}^n \binom{n}{i} (\frac{1}{n})^i < \sum_{i=0}^n \frac{1}{i!}$

$\iff \binom{n}{0} (\frac{1}{n})^0 + \binom{n}{1} (\frac{1}{n})^1 + \sum_{i=2}^n \binom{n}{i} (\frac{1}{n})^i < \frac{1}{0!} + \frac{1}{1!} + \sum_{i=2}^n \frac{1}{i!}$

$\iff 2 + \sum_{i=2}^n \binom{n}{i} (\frac{1}{n})^i < 2 + \sum_{i=2}^n \frac{1}{i!} \iff \sum_{i=2}^n \binom{n}{i} (\frac{1}{n})^i < \sum_{i=2}^n \frac{1}{i!}$

$\iff\sum_{i=2}^n \frac{n!}{i!(n-i)!n^i} < \sum_{i=2}^n \frac{1}{i!} $

$\iff \frac{n!}{(n-i)!n^i} < 1 , \forall i \ge 2$

Now I will prove by induction that $ \frac{n!}{(n-i)!n^i} < 1$ :

Let $n \in \Bbb{N}, n >1$

Let $P(i)::$ "$ \frac{n!}{(n-i)!n^i} < 1 , \forall i \ge 2$"

Base case:

$ \frac{n!}{(n-2)!n^2} = \frac{n(n-1)(n-2)!}{(n-2)!n^2} = \frac{n-1}{n} < 1$ so P(2) is true.

Inductive step:

(I assume as an inductive hypothesis that P(i) is true)

P(i+1) is true if we have $\frac{n!}{(n-(i+1))!n^{i+1}} < 1 \iff \frac{n!}{(n-i-1)!n^i n} < 1$

$\iff \frac{n!}{(n-i)!n^i} * \frac{n-i}{n} < 1 $

$\frac{n!}{(n-i)!n^i} < 1$ by the inductive hypothesis and $i \ge 2 \implies n-i < n \implies \frac{n-i}{n} < 1$.

So P(i+1) is true $\forall i \ge 2$

Is this correct? If it is not, what are my mistakes? And if it is, is there a less complicated proof (maybe without induction)?


By the binomial theorem $$\left(1+\tfrac{1}{n}\right)^n=1+n\cdot\frac{1}{n}+\tfrac{1}{2!}\left(1-\tfrac{1}{n}\right)+\tfrac{1}{3!}\left(1-\tfrac{1}{n}\right)\left(1-\tfrac{2}{n}\right)+...+\tfrac{1}{n!}\left(1-\tfrac{1}{n}\right)...\left(1-\tfrac{n-1}{n}\right)<$$ $$<2+\frac{1}{2!}+\frac{1}{3!}+...+\frac{1}{n!}.$$ I used $$\binom{n}{k}=\frac{1}{k!}\cdot n(n-1)...(n-k+1).$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.